Nanofibras eletrofiadas contendo caldo fermentado de paenibacillus polymyxa e nanopartículas de prata: produção, caracterização e avaliação da atividade antimicrobiana - Oliveira, Luís Fernando Rocha (Universidade Federal de São Carlos, 2023)
Chronic wounds have no defined recovery time, often leading to complications that can ultimately result in the patient's death. This scenario, combined with the growing number of multidrug-resistant bacterial cases, has intensified interest in researching new antimicrobials and more efficient delivery methods. Mats composed of electrospun nanofibers are promising platforms for drug delivery and wound dressing applications due to properties such as high surface area and porosity, which facilitate cell adhesion and mobility in the wound area. In this work, lyophilized fermented broth of Paenibacillus polymyxa (FBP) was incorporated into mats of poly(vinyl alcohol) (PVA) and poly(caprolactone) (PCL), biocompatible and biodegradable polymers, produced via electrospinning. Electrospun bilayer PVA/PCL mats containing FBP exhibited fewer fiber defects, and FTIR analysis confirmed FBP incorporation; however, the samples showed low antimicrobial activity even at higher FBP concentrations. To improve bioactivity, surface modifications were performed using silver nanoparticles (AgNPs), well-known nanostructures for their potent antimicrobial properties. Among the samples modified by spraying and immersion, the latter showed better antimicrobial responses; however, the method led to PVA dilution. By removing PVA from the formulation, PCL/FBP25% mats were obtained, which, when modified with AgNPs via immersion, exhibited the highest antimicrobial activity in the study. Additionally, FBP incorporation improved PCL properties, such as wettability and fiber uniformity, highlighting the potential of these nanofibers for further studies in skin dressing applications.
Electrospun nanofibers containing fermented broth of paenibacillus polymyxa and silver nanoparticles: production, characterization, and evaluation of antimicrobial activity
Keywords: Caldo fermentado; Antimicrobiano; Nanofibras; Eletrofiação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES